2004
DOI: 10.1210/en.2003-1109
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2D Catalyze Steroid 21-Hydroxylation in the Brain

Abstract: mRNA of cytochrome P450 21-hydroxylase (P450c21) is expressed in the brain, but little is known about the enzymatic properties of P450c21 in the brain. In the present study, we showed, by using various recombinant cytochrome P450 (CYP)2D enzymes and anti-CYP2D4- or P450c21-specific antibodies, that rat brain microsomal steroid 21-hydroxylation is catalyzed not by P450c21, but by CYP2D isoforms. Rat CYP2D4 and human CYP2D6, which are the predominant CYP2D isoforms in the brain, possess 21-hydroxylation activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 40 publications
1
43
0
2
Order By: Relevance
“…15,18) Enzyme Assay and Quantification of 21-Hydroxylated Metabolites of PROG and ALLO Progesterone 21-hydroxylation activity was measured by the method described previously 29) with a minor modification. The incubation mixture consisted of microsomes from cells containing recombinant CYP2D4 (50 pmol/ml) or CYP2D6 (30 pmol/ml), 2, 5, 10, or 20 mM (for CYP2D4) or 4, 10, 25, or 100 mM (for CYP2D6) PROG, 0, 2, 5, 20 or 50 mM of the tested psychotropic drug, 1 mM NADPH, and 100 mM potassium phosphate buffer (pH 7.4) in a final volume of 0.5 ml.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…15,18) Enzyme Assay and Quantification of 21-Hydroxylated Metabolites of PROG and ALLO Progesterone 21-hydroxylation activity was measured by the method described previously 29) with a minor modification. The incubation mixture consisted of microsomes from cells containing recombinant CYP2D4 (50 pmol/ml) or CYP2D6 (30 pmol/ml), 2, 5, 10, or 20 mM (for CYP2D4) or 4, 10, 25, or 100 mM (for CYP2D6) PROG, 0, 2, 5, 20 or 50 mM of the tested psychotropic drug, 1 mM NADPH, and 100 mM potassium phosphate buffer (pH 7.4) in a final volume of 0.5 ml.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, CYP2D4 mRNA is expressed in the rat brain, 14,15) and the reverse transcriptase-polymerase chain reaction (RT-PCR) product from CYP2D4, the predominant CYP2D isoform in the rat brain, is more abundant in the cerebellum, striatum, pons, and medulla oblongata.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that the enzymatic activity of Cytochrome P450 21-hydroxylase (P450c21), the main cytochrome 450 enzyme responsible for converting 17-OH-progesterone and progesterone to GC precursors (11-deoxycortisol and 11-deoxycorticosterone respectively) in AGs, is almost absent from CNS tissues (Mellon and Miller, 1989), various brain areas are capable of locally altering the GCs levels via (i) cytochrome P450 2D (CYP2D) isoforms (like the CYP2D6 isoform in human brain, found in most corticolimbic areas, basal forebrain and cerebellum) (Miksys and Tyndale, 2004) which perform the steroid 21-hydroxylation (replacing P450c21 lack of activity within the brain) (Kishimoto et al, 2004), (ii) 11β-hydroxysteroid dehydrogenase (11βHSD), that either increase the turnover between active and inactive GCs (isoform 1, found in corticolimbic regions, hypothalamic areas, brainstem and cerebellum) or solely degrade active GCs to inactive molecules (isoform 2, found in GC-insensitive brain regions like the circumventricular organs) (de Kloet et al, 2009), (iii) cytochrome P450 11-betahydroxylase (P450c11β) enzyme (found in neocortex) responsible for converting GC precursors to active hormones (cortisol and corticosterone respectively), and (iv) 5a-reductase (found in hypothalamic areas, corticolimbic regions and circumventricular organs), which directs corticosterone precursors to other metabolic pathways (Mensah-Nyagan et al, 1999) (Table 2).…”
Section: Complex Dynamics Of Gcs Reaching the Brainmentioning
confidence: 99%